Closer Than the Jugular Vein: A Relativistic Interpretation of Divine Nearness Using the Null Interval of Light - M.Ae.S.I., Mohd Mudassir (Journal of Quranic Sciences and Research, 2026)
The Qur’anic verse “And We are closer to him than his jugular vein” in Surah Qaf 50:16 (The Qur’an, 50:16) speaks of a form of divine nearness that cannot be reduced to ordinary physical distance. This paper presents a reflective scientific analogy based on Einstein’s special relativity (Einstein, 1905; Taylor & Wheeler, 1992), especially the concept of the null interval followed by light. In special relativity, a light like path has a spacetime interval of zero, , meaning that no proper time elapses along the null trajectory. Strictly speaking, a photon does not possess a valid rest frame; therefore, this paper avoids treating the photon as an observer with a literal “perspective.” Instead, photon language is used only as a simplified conceptual analogy. The central argument is that if even a created phenomenon such as light challenges ordinary intuitions about distance, motion, and time, then divine nearness may be reflected upon as a reality beyond ordinary spatial proximity. The paper does not claim that Allah is physically like light, nor does it propose a physical mechanism, tunnel, or wormhole. Rather, it uses the null interval as a symbolic and educational analogy for understanding how Allah may be affirmed as transcendent above creation while also being nearer to the human being than the jugular vein.